Outcomes in patients with newly diagnosed TP53‐mutated acute myeloid leukemia with or without venetoclax‐based therapy. Issue 19 (28th June 2021) - Venugopal, Sangeetha; Shoukier, Mahran; Konopleva, Marina; Dinardo, Courtney D.; Ravandi, Farhad; Short, Nicholas J.; Andreeff, Michael; Borthakur, Gautam; Daver, Naval; Pemmaraju, Naveen; Sasaki, Koji; Montalban‐Bravo, Guillermo; et al.
Abstract : Background: Venetoclax (VEN) in combination with a hypomethylating agent (HMA) has become the standard of care for patients aged >75 years and for those not eligible for intensive chemotherapy who have newly diagnosed acute myeloid leukemia (AML). The benefit of VEN‐based therapy in patients who have newly diagnosed AML with mutations in the TP53 gene ( TP53 mut ) over standard therapy is undefined. Methods: In this single‐institutional, retrospective analysis, the authors assessed the clinical outcomes of 238 patients with newly diagnosed TP53 mut AML and compared the clinical characteristics, response to different therapies, and outcomes of those who received VEN‐based (n = 58) and non–VEN‐based (n = 180) regimens. Results: Patients who received VEN‐based regimens were older (aged >65 years: 81% vs 65%; P = .02) and had higher response rates (complete remission, 43% vs 32%; P = .06) than those who received non–VEN‐based regimens. Compared with patients who received non–VEN‐based regimens, no difference in overall survival (median, 6.6 vs 5.7 months; P = .4) or relapse‐free survival (median, 4.7 vs 3.5 months; P = .43) was observed in those who received VEN‐based regimens, regardless of age or intensity of treatment. Conclusions: The addition of VEN to standard treatment regimens did not improve outcomes in younger or older patients who had TP53 mut AML. These data highlight the need for novel therapies beyond VEN to improve the outcome of patients with TP53 mut AML. Abstract : The benefit of venetoclax‐based therapy over standard approaches in patients with newly diagnosed, TP53 ‐mutated acute myeloid leukemia (AML) needs to be better defined. Although the addition of venetoclax to standard therapy is associated with numerically higher response rates, there is no improvement in overall or relapse‐free survival compared with standard therapy in patients with newly diagnosed, TP53‐mutated AML.